Tarzan at the Earth's core - Burroughs, Edgar Rice, 1875-1950; Frazetta, Frank, 1928-2010 (Salt Lake City, UT : Project Gutenberg, 2023)
"Tarzan at the Earth's Core" by Edgar Rice Burroughs is a novel serialized from 1929 to 1930. When scientist Abner Perry sends a radio plea from Pellucidar, a prehistoric world at the Earth's core, Jason Gridley assembles a daring rescue expedition. He recruits Tarzan and builds an airship to reach this dangerous inner realm through the polar opening. Separated from their crew, Tarzan and Gridley must survive against primitive peoples and prehistoric beasts while searching for the lost explorer David Innes. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tarzan_at_the_Earth%27s_Core
Release date is 2023-05-20
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Tarzan (Fictitious character) -- Fiction; Fantasy fiction; Adventure stories; Earth (Planet) -- Core -- Fiction